ANALISIS CETAKAN INJEKSI PLASTIK IMPELLER POMPA AIR PADA KAPAL NELAYAN APLIKASI CAD/CAE/CAM - Nur Indah Indah; Ibnu Arrifin Arrifin (Program Studi Teknik Mesin Universitas Tarumanagara, 2021)
Most of the fishermen in Indonesia, using pumps to drain water in the ship. The use of pumps insea water often lead to rapid corrosion, especially on the impeller. Impeller manufacture of plasticmaterials is an alternative to solve this problem. Stages in the designing mould of plastic impeller is with3D and 2D drawing, choose a suitable polymer material, making mold of product, selecting componentsof mold and simulating the result. In designing mould of plastic impeller used software to simulate theplastic mould with mould parameters plastic inserts to get the best results before the completion ofproduction. As for plastic injection machine that is used to clamp force 1000 ton capacity with 8 pieces ineach injection products and using nylon material, 281,1oC temperature parameters, 62 sec of cycle timeand 80,552 MPa pressure.